Neo-Confucian self-cultivation - Keenan, Barry C., 1940- (Dimensions of Asian spirituality., 2011)
Approximately fifteen hundred years after Confucius, his ideas reasserted themselves in the formulation of a sophisticated program of personal self-cultivation. Neo-Confucians argued that humans are endowed with empathy and goodness at birth, an assumption now confirmed by evolutionary biologists. By following the Great Learning--eight steps in the process of personal development--Neo-Confucians showed how this innate endowment could provide the foundation for living morally. Neo-Confucian students did not follow a single manual elaborating each step of the Great Learning; instead they were exposed to age-appropriate texts, commentaries, and anthologies of Neo-Confucian thinkers, which gradually made clear the sequential process of personal development and its connection to social order. Neo-Confucian Self-Cultivation opens up in accessible prose the content of the eight-step process for today's reader as it examines the source of mainstream Neo-Confucian self-cultivation and its major crosscurrents from 1000 to 1900.